Assessment of Impact of Long-Cassette Standing X-Rays on Surgical Planning for Cervical Pathology: An International Survey of Spine Surgeons. Issue 5 (May 2016) - Ramchandran, Subaraman; Smith, Justin S.; Ailon, Tamir; Klineberg, Eric; Shaffrey, Christopher; Lafage, Virginie; Schwab, Frank; Bess, Shay; Daniels, Alan; Scheer, Justin K.; Protopsaltis, Themi S.; Arnold, Paul; et al.
Abstract : BACKGROUND: Understanding the role of regional segments of the spine in maintaining global balance has garnered significant attention recently. Long-cassette radiographs (LCR) are necessary to evaluate global spinopelvic alignment. However, it is unclear how LCRs impact operative decision-making for cervical spine pathology. OBJECTIVE: To evaluate whether the addition of LCRs results in changes to respondents' operative plans compared to standard imaging of the involved cervical spine in an international survey of spine surgeons. METHODS: Fifteen cases (5 control cases with normal and 10 test cases with abnormal global alignment) of cervical pathology were presented online with a vignette and cervical imaging. Surgeons were asked to select a surgical plan from 6 options, ranging from the least (1 point) to most (6 points) extensive. Cases were then reordered and presented again with LCRs and the same surgical plan question. RESULTS: One hundred fifty-seven surgeons completed the survey, of which 79% were spine fellowship trained. The mean response scores for surgical plan increased from 3.28 to 4.0 ( P = .003) for test cases with the addition of LCRs. However, no significant changes ( P = .10) were identified for the control cases. In 4 of the test cases with significant mid thoracic kyphosis, 29% of participants opted for the more extensive surgical options of extension to the mid and lower thoracic spine when they were provided with cervical imaging only, which significantly increased to 58.3% upon addition of LCRs. CONCLUSION: In planning for cervical spine surgery, surgeons should maintain a low threshold for obtaining LCRs to assess global spinopelvic alignment. ABBREVIATIONS: HRQOL, health-related quality of life LCR, long-cassette radiographs SVA, sagittal vertical axis